Controlling parasitic weed by fungus - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The parasitic weed striga, which destroys cereal crops across the savannah regions of West Africa, may soon be controlled by a soil fungus. Researchers from McGill University in Canada, supported by the International Development Research Centre,...